4
$\begingroup$

The equation I'm given is $$\large x^{\log_2(\sqrt{x})-1} = \sqrt{8}$$

I've tried on solving it and my best try is on the photo. Got stuck there and not sure how to proceed any further.

enter image description here

$\endgroup$
  • 2
    $\begingroup$ Looking over your work, for your last equation, substitute $u = \log_{2}(x)$ so you have a quadratic. $\endgroup$ – MathematicsStudent1122 Jun 11 '16 at 17:11
  • 1
    $\begingroup$ what about solving the second degree equation in $\log_2 x$ ? if you like it change the variable as $y=\log_2 x$ and solve $y^2-2y-3=0$ you'll get two solutions say $y_1$ and $y_2$ and then solve $\log_2 x=y_{1;2}$ $\endgroup$ – Renato Faraone Jun 11 '16 at 17:11
  • $\begingroup$ Yes, actually Overkillus has already done the harder part of the work! He only need to solve tha standard quadratic equation $\endgroup$ – guestDiego Jun 11 '16 at 17:17
7
$\begingroup$

$${ x }^{ \log _{ 2 }{ \left( \sqrt { x } \right) -1 } }=\sqrt { 8 } \\ \log _{ 2 }{ \left( { x }^{ \log _{ 2 }{ \left( \sqrt { x } \right) -1 } } \right) =\log _{ 2 }{ { 2 }^{ \frac { 3 }{ 2 } } } } \\ \left( \log _{ 2 }{ \left( \sqrt { x } \right) -1 } \right) \log _{ 2 }{ x } =\frac { 3 }{ 2 } \\ \left( \frac { 1 }{ 2 } \log _{ 2 }{ x } -1 \right) \log _{ 2 }{ x } =\frac { 3 }{ 2 } \\ \text{Let } \log _{ 2 }{ x } =t \text{ and substitute.}\\ { t }^{ 2 }-2t-3=0\\ \left( t+1 \right) \left( t-3 \right) =0\\ \log _{ 2 }{ x } =-1\Rightarrow x=0.5\\ \log _{ 2 }{ x } =3\Rightarrow x=8$$

$\endgroup$
  • $\begingroup$ domain shoud be positive since $\sqrt { x } >0\Rightarrow x>0$ so both are solution of equation $\endgroup$ – haqnatural Jun 11 '16 at 18:17
2
$\begingroup$

$$x^{\log_2(\sqrt{x})-1} = \sqrt{8}$$ $$\log_2(x^{\log_2(\sqrt{x})-1})=\log_2(\sqrt{8})$$ $$(\log_2(\sqrt{x})-1)\log_2(x)=\frac{1}{2}\log_2(8)$$ $$\frac{1}{2}\log_2(8)\Rightarrow\frac{3}{2}$$ $$\left(\frac{1}{2}\log_2(x)-1\right)\log_2(x)=\frac{3}{2}$$ $$\log_2(x)=u$$ $$\left(\frac{1}{2}u-1\right)u*2=\frac{3}{2}*2$$ $$u^2-2u-3=0$$ $$u=\frac{2+\sqrt{(-2)^2-4*1*(-3)}}{2}=3,u=\frac{2+\sqrt{(-2)^2-4*1*(-3)}}{2}=-1$$ $$\log_2(x)=3\Rightarrow x=8,\log_2(x)=-1\Rightarrow x=\frac{1}{2}$$ $$8^{\log_2(\sqrt{8})-1} = \sqrt{8},\frac{1}{2}^{\log_2(\sqrt{\frac{1}{2}})-1} = \sqrt{8}$$

$\endgroup$
1
$\begingroup$

Fill in details and be sure you understand what properties are being applied:

$$x^{\log_2\sqrt x-1}=\sqrt8\implies\left(\frac12\log_2x-1\right)\log_2x=\frac32\implies$$

$$\left(\log_2x\right)^2-2\log_2x-3=0\implies\left(\log_2x-3\right)\left(\log_2x+1\right)=0$$

Finish now the exercise...and observe the only really new thing from what you did is the very last step

$\endgroup$
1
$\begingroup$

$$\large\log_2\sqrt{x}=t\implies x=2^{2t}$$ $$\large{2^{2t(t-1)}}=2^{\frac{3}{2}} \implies 4t^2-4t-3=0\implies t_1=-\frac{1}{2}\,,\, t_2=\frac{3}{2}$$ then $$\large x_1=\frac{1}{2}\,\,,\,\, x_2=8$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.